Sleep-exercise dynamics and student well-being: insights from a Malaysian university student cohort / Muhammad Hairul Safri Ishak and Azman Ahmad Tajri - Ishak, Muhammad Hairul Safri; Ahmad Tajri, Azman (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study explores the correlation between sleep quality and physical activity among FSR students at UiTM Seremban 3. By examining sleep patterns, activity levels, and their interrelationship, this research aims to uncover significant behavioral insights, addressing a growing need for health-related awareness among university students [1,2]. A quantitative, non-experimental survey design was employed using questionnaires to assess sleep quality and physical activity. A random sampling method was applied to select 333 participants from a population of 1,000, ensuring representativeness. Standardized tools measured sleep quality and activity levels, adhering to Krejcie and Morgan's guidelines for sample size determination.